Social determinants of mental health of women living in slum: a systematic review - Fatemeh Abdi; Fatemeh Alsadat Rahnemaei; Parisa Shojaei; Fatemeh Afsahi; Zohreh Mahmoodi (Korean Society of Obstetrics and Gynecology, 2021)
Objective With the rise of urbanization globally, the problem of living in slums has become a problem for the civil society. As a vulnerable segment, women make up half of the population in these regions; therefore, women's mental health has always been a concern. The purpose of this study was to review the social determinants of mental health in women living in slum areas. Methods We systematically reviewed articles published between 2009 and 2019 on the social determinants of women's mental health in SID, Magiran, Google scholar, PubMed, Scopus, Science Direct, Embase, MEDLINE, PsychINFO, and PsychARTICLES databases using MeSH keywords according to PRISMA guidelines. The quality of the studies was assessed depending on the type of study using Ottawa Newcastle" scale and Joanna Briggs Institute quality assessment tools. Finally, 23 studies were analyzed. Results Different social determinants influenced the mental health of women living in slum areas. Among the structural determinants, the socioeconomic level had the highest frequency, and gender was in the second rank with the highest correlation with poorer women's mental health status. Among the intermediate determinants, living conditions, food insecurity, social capital, and social support were most frequently associated with mental health status. Conclusion Women living in slum areas are prone to developing mental disorders and poorer mental health; therefore, supporting these women and creating job opportunities to raise their incomes and, subsequently, improve their social, economic, and living conditions should be taken into consideration. In addition, this requires careful planning and comprehensive social support.